Box their SOXes off. - Bostick, John (New York ACM, 2006)
Being proactive with SAS 70 Type II audits helps both parties in a vendor relationship.
Keywords: Computing Milieux; Management of Computing and Information Systems; General; Legal aspects of computing; Governmental issues; Regulation